MINAT DAN BAKAT SISWA PADA EKSTRAKURIKULER OLAHRAGA DI SMP NEGERI 2 TONJONG - Szalsa Shabrina; Ramdhani Rahman; Dani Nurdiansyah; Didi Muhtarom (Journal of Physical Education and Sport Science, 2022)
Students' Interests and Talents in Extracurricular Sports at SMP Negeri 2 Tonjong, Health and Recreation Physical Education Study Program, 2018, 57 pages. There are 3 extracurricular sports at SMP Negeri 2 Tonjong, Tonjong District, namely: 1). Futsal, 2). Volleyball and 3). Basketball, with a total of 120 students. It is not yet known whether the student's talent matches the student's interest in the sport they are participating in. One way to identify talent is using Sport Search software. This study aims to determine the suitability of students' interests and talents in extracurricular sports at SMP Negeri 2 Tonjong, Brebes Regency in 2022. This study uses a quantitative type and uses descriptive survey methods and tests. The sample used in this study is sample Random Sampling. The sample in this population was taken from participants in extracurricular sports at SMP Negeri 2 Tonjong, Brebes Regency, which amounted to 120 people to 30 students. Data were collected through observation and tests. The results of this study are 11 students or 36.7% have criteria according to talent in sports, 19 students or 63.3% .